Safety, Tissue Distribution, and Metabolism of LNA-Containing Antisense Oligonucleotides in Rats. (August 2021) - Romero-Palomo, Fernando; Festag, Matthias; Lenz, Barbara; Schadt, Simone; Brink, Andreas; Kipar, Anja; Steinhuber, Bernd; Husser, Christophe; Koller, Erich; Sewing, Sabine; Tessier, Yann; Dzygiel, Pawel; et al.
Antisense oligonucleotides (ASOs) are chemically modified nucleic acids with therapeutic potential, some of which have been approved for marketing. We performed a study in rats to investigate mechanisms of toxicity after administration of 3 tool locked nucleic acid (LNA)-containing ASOs with differing established safety profiles. Four male rats per group were dosed once, 3, or 6 times subcutaneously, with 7 days between dosing, and sacrificed 3 days after the last dose. These ASOs were either unconjugated (naked) or conjugated with N-acetylgalactosamine for hepatocyte-targeted delivery. The main readouts were in-life monitoring, clinical and anatomic pathology, exposure assessment and metabolite identification in liver and kidney by liquid chromatography coupled to tandem mass spectrometry, ASO detection in liver and kidney by immunohistochemistry, in situ hybridization, immune electron microscopy, and matrix-assisted laser desorption/ionization mass spectrometry imaging. The highly toxic compounds showed the greatest amount of metabolites and a low degree of tissue accumulation. This study reveals different patterns of cell death associated with toxicity in liver (apoptosis and necrosis) and kidney (necrosis only) and provides new ultrastructural insights on the tissue accumulation of ASOs. We observed that the immunostimulatory properties of ASOs can be either primary from sequence-dependent properties or secondary to cell necrosis.